A Survey Research on the Use of Mobile Applications in Software Project Management - Carvalho, Elielton da Costa; Malcher, Paulo R. Campelo; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
For several decades, project management (PM) was carried out in a traditional way, mostly without the aid of software tools. This scenario changed so that several PM information systems have been developed to assist project managers in many fields, including software projects. Similar to other systems, such tools started operating in mobile devices, given increasing adoption and use. Therefore, a study on how mobile applications have been used to manage software projects becomes important. In this paper, we report on a survey research carried out with 75 software project managers to identify the most used mobile applications and where they are mostly applied in PM. A quantitative analysis shows that 57% of the participants do not use mobile PM applications. However, mobile applications such as Trello, Jira and Redmine are mostly used by software project managers. A qualitative analysis was carried out to understand the reasons that lead software project managers to avoid those tools, such as: lack of effectiveness, lack of resources, lack of stimulation, diversity of tools, project complexity, and lack of qualified practitioners. This study brings some improvement suggestions on the existing tools as well as demands for new ones towards a more effective project management support.